Why concepts matter: translating social and political thought - Burke, Martin J.; Richter, Melvin (Studies in the history of political thought, 2012)
The volume explores distinctive issues involved in translating political and social thought. Thirteen contributors consider problems arising from the study of translation and cultural transfers of texts, in particular in terms of translation studies, and the history of concepts (Begriffsgeschichte)